Microbiological Investigation of O‐Serogroups, Virulence Factors and Antimicrobial Resistance Properties of Shiga Toxin‐Producing Escherichia Coli Isolated from Ostrich, Turkey and Quail Meats. Issue 4 (12th May 2015) - Hemmatinezhad, Behsan; Khamesipour, Faham; Mohammadi, Milad; Safarpoor Dehkordi, Farhad; Mashak, Zohreh
Abstract From clinical and microbiological perspectives, it is important to know which serogroups, virulence, and antibiotic resistance genes and antibiotic resistance patterns are present in Shiga toxin‐producing Escherichia coli strains in poultry meats from turkey, quail and ostrich that have recently been added to the cart households. These were investigated in the present study. Five‐hundred poultry meat samples were collected from the supermarkets of Isfahan province, Iran. Samples were cultured immediately and those that were E. coli‐positive were analyzed for the presence of serogroups, antibiotic resistance genes and bacterial virulence factors. Antimicrobial susceptibility was performed using disk diffusion method. The prevalence rates of E. coli in ostrich, turkey and quail meat samples were 9.33, 23.52 and 27.77%, respectively. All of the enterohemorrhagic E. coli subtypes were positive for stx1, eae and ehly genes. The prevalence rate of stx1 gene in all attaching and effacing E. coli isolates was 100%. A significant difference was found between the frequency of AEEC (enteroadherent E. coli) and EHEC (enterohemorrhagic E. coli) subtypes (P < 0.05). Among all serogroups studied, O26 and O157 had the highest prevalence. The most commonly detected antibiotic resistance genes in various poultry meat samples were tetA, CITM and aac(3)‐IV. The highest level of antibiotic resistance was observed against tetracycline, ampicillin and gentamicin. Resistance against sulfamethoxazole and enrofloxacin was intermediate. Our findings should raise awareness about antibiotic resistance in poultry meats in Iran. It seems that sanitary conditions were not observed in Iranian poultry farms, slaughterhouses and supermarkets. Practical Applications Recognition of the new epidemiological aspects of Shiga toxigenic Escherichia coli helps us to know the exact routes of transmission and decisive origin of this bacterium. Consumption of ostrich, quail and turkey meats is popular among Iranian people, but there is no accurate inspection on their meats and carcasses. Quail and turkey meat samples were the most commonly contaminated, suggesting that they may be the reservoir of E. coli. High prevalence of virulence factors, antibiotic resistance genes and antibiotic resistance has also been reported. Due to the lower levels of antibiotic resistance, prescription of streptomycin, cephalothin and trimethoprim has been suggested for the treatment of food poisoning due to the Shiga toxigenic E. coli strains of bird meat.